The Effect of Capital Structure (Debt to Equity Ratio and Debt to Asset Ratio) on Profitability (Return on Asset) of Manufacturing Companies in the Consumer Goods Sub-Sector Listed on the IDX During the COVID-19 Pandemic - Hanifan, Zakie; Agung, Syahrum; Sri Wahyuni, Neng Ayu (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2025)
This study aims to analyze the influence of capital structure proxied with Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR) on profitability proxied by Return on Asset (ROA) in manufacturing companies in the consumer goods sub-sector listed on the Indonesia Stock Exchange (IDX) during the COVID-19 pandemic period 2020-2021. The research method used is quantitative causality with secondary data in the form of annual financial statements. The research population is all manufacturing companies in the consumer goods sub-sector on the IDX. The sample was determined using purposive sampling techniques with the criteria of registered companies during 2020-2021, issuing complete financial statements, and not delisting, so that 45 companies were obtained with a total of 90 observations. Data analysis techniques include descriptive statistics, classical assumption tests (normality, multicollinearity, heteroscedasticity, autocorrelation), multiple linear regression analysis (OLS), t-test, F test, and determination coefficient (R²). The results showed that partially, DER had a significant negative effect on ROA with a t-count value of -2.845 (sig. 0.006) and DAR had a significant negative effect on ROA with a t-count value of -2.103 (sig. 0.039). Simultaneously, DER and DAR together had a significant effect on ROA with an F-count value of 5.876 (sig. 0.004). A coefficient of determination (R²) value of 0.174 indicates that 17.4% of ROA variations can be explained by DER and DAR, while the remaining 82.6% are explained by other variables outside the model. These findings confirm that during the COVID-19 pandemic, increased debt will decrease the company's profitability, so management needs to be careful in making funding decisions in times of crisis.